Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1371/journal.ppat.1000775
|View full text |Cite
|
Sign up to set email alerts
|

A New Nuclear Function of the Entamoeba histolytica Glycolytic Enzyme Enolase: The Metabolic Regulation of Cytosine-5 Methyltransferase 2 (Dnmt2) Activity

Abstract: Cytosine-5 methyltransferases of the Dnmt2 family function as DNA and tRNA methyltransferases. Insight into the role and biological significance of Dnmt2 is greatly hampered by a lack of knowledge about its protein interactions. In this report, we address the subject of protein interaction by identifying enolase through a yeast two-hybrid screen as a Dnmt2-binding protein. Enolase, which is known to catalyze the conversion of 2-phosphoglycerate (2-PG) to phosphoenolpyruvate (PEP), was shown to have both a cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…In fact, actin has an essential transcriptional role in the nucleus (60 -62). Actin serves as a scaffold to assist in gene regulation and also is a key component in nuclear export, as suggested by the leucine-rich nuclear export signal within actin that has aided in nuclear export of viral RNA (63,64). Thus, we hypothesize that the changes in interactions between ER␤ and actin-associated proteins such as GELS and ENO1, which has been shown to modulate DNA methyltransferase (65), could be a result of changes in nuclear actin structure (59).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, actin has an essential transcriptional role in the nucleus (60 -62). Actin serves as a scaffold to assist in gene regulation and also is a key component in nuclear export, as suggested by the leucine-rich nuclear export signal within actin that has aided in nuclear export of viral RNA (63,64). Thus, we hypothesize that the changes in interactions between ER␤ and actin-associated proteins such as GELS and ENO1, which has been shown to modulate DNA methyltransferase (65), could be a result of changes in nuclear actin structure (59).…”
Section: Discussionmentioning
confidence: 97%
“…histolytica belongs to the so-called family of "Dnmt2-only" organisms, in that it does not contain any of the canonical DNA methyltransferases (Dnmt1 and Dnmt3). E. histolytica Dnmt2 (Ehmeth) is a weak, but genuine, DNA methyltransferase (6)(7)(8), and its ability to catalyze tRNA Asp methylation has been recently demonstrated (9). This dual specificity of Ehmeth for DNA and tRNA has also been proposed for the Dnmt2 homolog in Drosophila melanogaster (10).…”
Section: A Moebiasis Is a Parasitic Infection Of The Human Intestine mentioning
confidence: 99%
“…We have recently reported that glucose starvation, with the help of the glycolytic enzyme enolase, regulates the parasite's methylation status (9). Enolase interacts with the catalytic site of Ehmeth and inhibits its methyltransferase activity.…”
Section: A Moebiasis Is a Parasitic Infection Of The Human Intestine mentioning
confidence: 99%
“…Moreover, homologs have been found in many organisms outside of vertebrates including Schizosaccharomyces pombe, Dictyostelium discoideum, Entamoeba hystolitica, and the bacterium Geobacter sulfurreducens, to name a few. [60][61][62][63] Limitations of the RNA modification mapping approach One limitation of the traditional RNA modification mapping approach by MS is the reliance on mass differences to identify the sequence location for a modified nucleoside. Modifications that share the same mass value, e.g., methylations such as 7-methylguanosine (m 7 G), 1-methylguanosine (m 1 G), N 2 -methylguanosine (m 2 G) and 2'-O-methylguanosine, cannot be differentiated within the MS/MS data.…”
Section: Rna Modification Mapping Of Trnas and Rrnasmentioning
confidence: 99%